Chalcone derivatives from the root bark of Morus alba L. act as inhibitors of PTP1B and α-glucosidase. (November 2018) - Ha, Manh Tuan; Seong, Su Hui; Nguyen, Tien Dat; Cho, Won-Kyung; Ah, Kim Jeong; Ma, Jin Yeul; Woo, Mi Hee; Choi, Jae Sue; Min, Byung Sun
Abstract: As part of our continuing research to obtain pharmacologically active compounds from Morus alba L. (Moraceae), four Diels-Alder type adducts (DAs) [morusalbins A−D], one isoprenylated flavonoid [albanin T], together with twenty-one known phenolic compounds were isolated from its root bark. The chemical structures were established using NMR, MS, and ECD spectra. The DAs including morusalbins A−D, albasin B, macrourin G, yunanensin A, mulberrofuran G and K, and albanol B exhibited strong inhibitory activities against both protein tyrosine phosphatase 1B (PTP1B) (IC50, 1.90− 9.67 μM) and α-glucosidase (IC50, 2.29− 5.91 μM). In the kinetic study, morusalbin D, albasin B, and macrourin G showed noncompetitive PTP1B inhibition, with K i values of 0.33, 1.00, and 1.09 μM, respectively. In contrast, these DAs together with yunanensin A produced competitive inhibition of α -glucosidase, with K i values of 0.64, 0.42, 2.42, and 1.19 μM, respectively. Furthermore, molecular docking studies revealed that these active DAs have high affinity and tight binding capacity towards the active site of PTP1B and α -glucosidase. Graphical abstract: Four Diels-Alder adducts, one isoprenylated flavonoid, and 21 known phenolic compounds were isolated from Morus alba root bark. The active Diels-Alder adducts could act as dual allosteric PTP1B/catalytic α -glucosidase inhibitors. Highlights: . Four Diels-Alder adducts (DAs) and one isoprenylated flavonoid were isolated from Morus alba Absolute configuration of DAs with a bicyclo[3.3.1] core was confirmed for the first time by calculated ECD. Some of the DAs showed potent inhibition of both PTP1B and α-glucosidase. The active DAs could act as dual allosteric PTP1B/ catalytic α -glucosidase inhibitors.